2020
DOI: 10.21037/jtd.2019.12.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the short-term outcomes of robot-assisted minimally invasive, video-assisted minimally invasive, and open esophagectomy

Abstract: Background: The development of minimally invasive surgery has initiated many changes in the surgical treatment of esophageal cancer (EC) patients. The aim of this study was to compare the short-term outcomes of robotic-assisted minimally invasive esophagectomy (RAMIE), video-assisted minimally invasive esophagectomy (VAMIE), and open esophagectomy (OE). Methods: Our study included patients who had undergone McKeown esophagectomy at Tianjin Medical University Cancer Institute and Hospital between January 2016 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(80 citation statements)
references
References 24 publications
(27 reference statements)
0
80
0
Order By: Relevance
“…There have been four studies which compared RAMIE and MIE where the methods of recurrent nerve dissection were described in detail and the number of harvested recurrent nerve lymph nodes was five or more. 14,55,60,61 All these studies reported that the rate of recurrent nerve injury is lower in RAMIE than in MIE. Recurrent laryngeal nerve injury leads to serious complications such as aspiration pneumonia.…”
Section: Iss Ec Ti On Of Recurrent Nerve Lymph Node Smentioning
confidence: 98%
See 1 more Smart Citation
“…There have been four studies which compared RAMIE and MIE where the methods of recurrent nerve dissection were described in detail and the number of harvested recurrent nerve lymph nodes was five or more. 14,55,60,61 All these studies reported that the rate of recurrent nerve injury is lower in RAMIE than in MIE. Recurrent laryngeal nerve injury leads to serious complications such as aspiration pneumonia.…”
Section: Iss Ec Ti On Of Recurrent Nerve Lymph Node Smentioning
confidence: 98%
“…Therefore, comparison of recurrent nerve injury rate between the studies does not directly translate into the comparison of the quality of esophageal surgery. There have been four studies which compared RAMIE and MIE where the methods of recurrent nerve dissection were described in detail and the number of harvested recurrent nerve lymph nodes was five or more 14,55,60,61 . All these studies reported that the rate of recurrent nerve injury is lower in RAMIE than in MIE.…”
Section: Dissection Of Recurrent Nerve Lymph Nodesmentioning
confidence: 99%
“…Intraoperative outcomes are shown in Figure 7. Operative time was reported by 9 Authors [11,35,37,38,41,45,46,61,63] were performed with a fully robotic approach, except for the study by Rolff et al [45], in which an hybrid procedure (robotic approach to the abdomen and open approach to the thorax) was used. Two articles reported on Ivor-Lewis procedure [37,39], one on McKeown esophagectomy [61] while ten did not provide relevant data to allow subgroup analysis [11,35,41,[44][45][46]52,[62][63][64].…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…Operative time was reported by 9 Authors [11,35,37,38,41,45,46,61,63] Postoperative complications are shown in Figure 8. Anastomotic leakage was analysed by 8 Authors [11,35,39,41,44,46,61,63] on 2188 procedures (823 robotic and 1365 open), with no statistical differences between the two approaches (OR = 0.953, p = 0.799, 95%CI 0.655; 1.385) and no significant heterogeneity among the studies (I 2 = 0%, p = 0.556). Postoperative bleeding was reported by 4 Authors [11,46,61,63] on 818 procedures (339 robotic and 479 open), demonstrating no significant differences between the two groups (RD = −0.007, p = 0.372, 95%CI −0.022; 0.008) and no significant heterogeneity among the studies (I 2 = 0%, p = 0.439).…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…19 Although MIE traditionally has used videoscopic assistance, robotic techniques currently are being integrated to increase exposure with a 3-dimensional field visualization. 20 Regardless of the chosen method, the bottom line when adopting new surgical approaches is patient outcomes. From a surgical standpoint and despite early skepticism, MIE meets this standard, with potential added benefits including fewer respiratory complications, less blood loss, less pain, earlier oral intake, and enhanced recovery of quality of living.…”
mentioning
confidence: 99%